LEGAL REGULATION OF PERSONAL DATA PROTECTION - Pokhylenko, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose: the purpose of the article is to determine peculiarities of the protection of personal data and, on the basis of the analysis of legal literature and normative legal acts, to propose an author’s definition of the said concept. Research methods: by using a dialectical cognition method to concentrate accumulated scientific knowledge and practice of applying the current legislation for the implementation of the protection of personal data. Results: based on the analysis of legal literature and national legislation, the author proposes original definitions. Personal data is any information related to an identified or identifiable natural person. In other words, personal data is information that allows the unique identification of the individual it pertains to. This definition relies on two criteria: Identification: a person can be identified either directly (e.g., by surname, first name, patronymic, date of birth, etc.) or indirectly (e.g., by phone number, email address, IP address, etc.). Possibility of identification: a person can be identified with the help of additional information available to the personal data controller. Thus, the following information may be considered as personal data: Identification data (surname, first name, patronymic, date of birth, place of birth, taxpayer identification number, passport number, etc.); Contact data (address, phone number, email address, etc.); Some biometric data (fingerprints, facial images, etc.); Some medical data (health status, medical diagnoses, etc.); Some financial data (bank account information, credit card details, etc.); Some education and professional activity data; Some online activity data (web browsing history, cookies, etc.). Personal data protection is a set of measures aimed at preventing unauthorized access, use, disclosure, destruction, or alteration of personal data. Discussion: features of personal data protection, problems of determining the principles of personal data processing.